Rapid trend towards larger and more moisture-limited trees in Central-European temperate forests - Václav Treml; Jan Tumajer; Filip Oulehle; Jan Altman; Jiří Doležal; Monika Vejpustková; Miloš Rydval; Nela Altmanová; Lukáš Brůha; Vojtěch Čada; Pavel Fibich; Ryszard Kaczka; et al. (Environmental Research Letters, 2025)
Tree stems represent a long-lived biomass compartment for atmospheric carbon sequestration. While terrestrial biosphere models predict rising carbon sequestration in forests, direct observations of tree growth are inconclusive due to varying standardization procedures of tree-ring series and complex factors influencing stem growth such as moisture and nutrient deficits and anthropogenic carbon and nitrogen fertilization. The mismatch between tree-ring-based observations, repeated inventories at permanent plots, and predictions of biospheric models represents a significant knowledge gap limiting forecasting of future forest growth. Using the novel approach free of tree-ring standardization trials and focusing on even-aged trees sampled from uneven-aged forest stands, we present a robust comparison of tree stem diameter changes in temperate forests between 1990 and 2015 along environmental gradients in Central Europe. The stem sizes of four out of five species showed significant enlargement while also partly increasing stem growth limitation due to moisture availability. The largest increase in stem diameter was recorded for late succession species on fertile sites. By contrast, the stem size of early-succession species on dry and nutrient-poor sites remained unaltered. Stems of mature trees in present-day forests are, on average, 8% thicker than their counterparts in 1990 consistent with trends predicted by terrestrial biosphere models. We demonstrated that, despite increasing drought limitation, temperate tree species enlarged their stems. Viewed in conjunction with older permanent plot data, Central-European temperate forests exhibited almost half century of continuous stem enlargement, potentially impacting forest functioning in terms of size-sensitive characteristics such as susceptibility to drought and disturbances.